Sprawiedliwość gotowa na miłosierdzie (Rdz 18,16-33)? - Lemański, Janusz (Verbum Vitae, 2003)
Contemporary biblical studies find it difficult to determine the date of Gen 18,16-33. Although most of the scholars agree that the final editor of the text must have been under a strong influence of the deuteronomistic as well as sapiential language and ideas. The aim of this article is to point out a new concept of God’s justice developed in the story of Abraham’s discourse with God. Using the metbod of egzegetical analysis tbe author shows how the theological understanding of justice in this text developes towards the idea of charity where a small group of rightenous men (10 in number) is anabled to save a majority of siners. This new theological meaning of God’s justice may be comprised somewhere between Ez 14,12-23 and Jr 5,1; Ez 22,30, finaily finds its summit in Is 53.